Rapid detection of Trypanosoma cruzi by colorimetric loop-mediated isothermal amplification (LAMP): A potential novel tool for the detection of congenital Chagas infection - Rivero, Rocio (2017)
Fil: Rivero, Rocio. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.